Analisis Potensi Usaha Ayam Broiler dan Usaha Pertanian di Kabupaten Jepara - Moch Aminnudin; Nurul Huda; Moch Imron; Hamdi Sarimaryoni (Universitas Pasir Pengaraian, 2024)
The aim of the research is to analyze the potential of broiler chicken businesses and agricultural businesses. The research was conducted in Jepara Regency as a central area for the agricultural sector. The research uses LQ and DLQ analysis to analyze business potential. The average LQ and DLQ results for agricultural businesses are 1.5 and 1.54. Meanwhile, the LQ and DLQ of the broiler chicken business are 1.54 and 2.06 and 2.28. This indication shows that the broiler business is considered high class, meaning that the broiler business is able to dominate or become a leading sector in the Jepara region